Involvement of cannabinoid receptors in depression of the putative nociceptive response in spinal cord preparations isolated from neonatal rats - Kayo Tsuzawa; Hiroshi Onimaru; Katsunori Inagaki; Masahiko Izumizaki (Journal of Physiological Sciences)
Abstract A metabolite of acetaminophen, AM404, which is an anandamide transporter inhibitor, induces analgesia mainly via activation of transient receptor potential channel 1 in the spinal cord, although the role of cannabinoid receptors remains to be studied. The ventral root reflex response induced by stimulation of the dorsal root in in vitro preparations of rat spinal cord is useful to assess the effect of analgesics. We analyzed the effects of AM404 and cannabinoid receptor antagonist AM251 on reflex responses in lumbar spinal cord preparations from newborn rats and found that the amplitude of the slow ventral root potential after administration of 10 µM AM404 was not significantly changed, whereas 10 µM AM251 significantly increased the amplitude. Administration of the cannabinoid receptor 1 agonist WIN55,212-2 (10 µM) did not significantly affect the reflex response. We suggest that endogenous cannabinoids in the spinal cord are involved in the antinociceptive mechanism through suppressive effects.